A process for distributed software evolution: a proprietary software case study - Camilo, Joao Ricardo M.; L'Erario, Alexandre; Pagotto, Tiago; Fabri, Jose Augusto (Proceedings of the 13th International Conference on Global Software Engineering, 2018)
Proprietary enterprise software is commonly embedded in multinational organizations and therefore has multiple sources of global or local demand. This type of software is subject to constant evolutions motivated by improvements in the features or by changes in the legal and economic context of its environment. Problems arising from the demand for requirements are associated with the suitability of a particular local requirement to its global context, for example: tax rules are characteristic of a specific country while a business rule can achieve every global structure. In addition, software customization can be implemented by the software producer, external partners, programmers allocated within the customer company, and so on. The coordination of this scenario is considered critical for the productive sector company that uses proprietary enterprise software. If the software does not evolve, the company processes can be temporarily compromised, and the software becomes obsolete. We report a case study of a large proprietary ERP system in a multinational company located in Brazil that is among the three largest exporters in its market segment. As a contribution, we present the current structure of the distributed evolution process of the software in question and how the stakeholder coordination of this scenario occurs.